2012
DOI: 10.1021/la303250e
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Heating by Optical Electromagnetic Irradiation

Abstract: The dissipative absorption of electromagnetic energy by 1D nanoscale structures at optical frequencies is applicable to several important phenomena, including biomedical photothermal theranostics, nanoscale photovoltaic materials, atmospheric aerosols, and integrated photonic devices. Closed-form analytical calculations are presented for the temperature rise within infinite circular cylinders with nanometer-scale diameters (nanowires) that are irradiated at right angles by a continuous-wave laser source polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…Recently, a 2-D silicon PC was shown to increase absorption efficiency of photovoltaic cells by 31% when compared with a c-Si film with a distributed Bragg reflector [20]. Additionally, analytical theory has shown that morphology-dependent res- onances can enhance internal fields in silicon nanowires [21]. Experimental results have demonstrated increased absorption in nanowire-patterned silicon as compared with planar silicon across the visible and near-infrared regions of the electromagnetic spectrum [22].…”
mentioning
confidence: 99%
“…Recently, a 2-D silicon PC was shown to increase absorption efficiency of photovoltaic cells by 31% when compared with a c-Si film with a distributed Bragg reflector [20]. Additionally, analytical theory has shown that morphology-dependent res- onances can enhance internal fields in silicon nanowires [21]. Experimental results have demonstrated increased absorption in nanowire-patterned silicon as compared with planar silicon across the visible and near-infrared regions of the electromagnetic spectrum [22].…”
mentioning
confidence: 99%
“… The normalized electric field distribution, E·E*/E02 , for an infinitely long 500 nm diameter silicon cylinder in water irradiated with λ 0 =980 nm (a) using the analytical results of Bohren and Huffman and (b) using MEEP. Figure reproduced with permission from reference copyright the American Chemical Society.…”
Section: Photothermal Heating Theorymentioning
confidence: 99%
“…Generally, the source term Q ( r , t ) is dependent on the complex internal electric fields generated by irradiation as well as the electrical conductivity at optical frequencies and is given by 88 : Q(boldr,t)=12σtrueE~(boldr,t)boldE~(boldr,t) where E ( r , t ) and E *( r , t ) are the generated electric field within the NP and its complex conjugate, respectively 88 . The electrical conductivity at optical frequencies is given by 89 : σ=4πnkλiμc where λ i is the incident wavelength, μ is the nanoparticles relative magnetic permeability, c is the speed of light, and n and k are the real and imaginary parts of the index of refraction of the nanoparticle, respectively 88 .…”
Section: Introductionmentioning
confidence: 99%